PENATALAKSANAAN GIGI PREMOLAR KEDUA MAKSILA DENGAN SALURAN AKAR VERTUCCI TIPE V - laporan Kasus - Arlina Nurhapsari (Odonto : Dental Journal, 2014)
Background: The aim of the case report is to demonstrate the importance of knowing the root canals configuration in the maxillary second premolars. Maxillary second premolars usually have one root canal, however in several cases there is more than one root canal with a variety of configurations. Method: multiple visit root canal treatment with a crown down technique on the maxillary second premolar with unusual root canals configuration which is confirmed using radiograph. Result: Based on radiograph, it was identified Vertucci type V root canal on the maxillary second premolars. After biomechanical preparation, obturation was conducted. When patient controlled, there were not problem and inflammation. Conclusion : This report described and discussed about the possibility of root canals variation on the maxillary second premolars. Careful examination using radiograph and deep knowledge, it is identified by the clinician in treating root canal treatment on that premolars.